Natrium Urin Petanda Surrogate Brain Natriuretic Peptide Plasma Pasien Infark Miokard dengan Elevasi ST? - Januar W Martha; Hariadi Hariawan; S Taofan; Nani Hersunarti; Bambang B Siswanto (Jurnal Kardiologi Indonesia, 2007)
Background. High level of Brain Natriuretic Peptide (BNP) was suspected as a predictor of adverse events in acute ST Elevation Myocardial Infarc-tion (STEMI). Unfortunately, the cost and availability of BNP assay had hampered its use. Natriuresis is one of the hallmark effect of raised BNP and measuring urinary sodium might offer insight to the plasma BNP. This study aims to search for any correlation between measured plasma BNP and urinary sodium in patients presenting with acute STEMI.Methods. In an observational descriptive analytic study, we selectively in-cluded patients presenting with acute STEMI and checked for plasma BNP and urinary sodium. All patients had no symptoms or therapy of heart failure prior to admission, had no prior MI, had no valvular abnormalities, and had normal renal function. Plasma BNP was tested using immunoassay method from Abbot Diagnostics, while urinary sodium with ionic specific electrode method. Specimen for plasma BNP were taken at the admission while urinary sodium in the next morning, taking account of urine volume. Results. There were 17 patients, 15 were (82.4%) men, with age 55.1+8.2 years old, onset of STEMI 18.6+2.3 hours, and left ventricular ejection fraction (LVEF) 47.6+11.6%. The urinary sodium was 85.1+34.3 mEq/L, and plasma BNP 449.7+48.8 pg/ml. Pearson’s correlation and linear re-gression analysis showed positive correlation between urinary sodium and plasma BNP (r = 0.71). In multivariate analysis, plasma BNP (p<0.01) and LVEF (p<0.05) were the major influencing factors for urinary sodium level.Conclusion.This study revealed a strong correlation between plasma BNP and urinary sodium in patients presenting with acute STEMI. While mea-surement of urinary sodium cannot replace plasma BNP, it might actually reflect plasma BNP level.